Microwave/RF applicators and probes for material heating, sensing, and plasma generation - Mehdizadeh, Mehrdad (William Andrew, an imprint of Elsevier, 2015)
This edition encompasses the area of high-frequency applicators and probes for material interactions as an integrated science. Based on practical experience rather than entirely on theoretical concepts, and emphasizing phenomenological explanations and well-annotated figures, the book represents one of the most important resources on the topics of microwave technologies, applications of RF and microwaves in industry (industrial heating and drying), and microwave engineering. Topics include: basics of field-material interactions; probes and applicators, demonstrates their real-world applications, and offers numerically solved examples; new information on how the interactions of electromagnetic fields with materials at high frequencies have given rise to a vast array of practical applications in industry, science, medicine, and consumer markets. --